Alternative water sources for residential irrigation systems: A case study from Istanbul (International Journal of Irrigation and Water Management, 2017)
Water is the primary life-giving resource and hence requires careful preservation. Choosing an irrigation system, which uses an alternative water source such as graywater or harvested rainwater will help this preservation. The intent of this study is to compare residential irrigation system designs that draw their water source from graywater, harvested rainwater or municipal water. For realizing this comparison, the following criteria were evaluated: Availability of water, system components, cost and maintenance. In conclusion, this study found that municipal water is still an economically feasible source for residential system in Istanbul, despite the fact that graywater and harvested rainwater are the preferred sources in terms of sustainability.